THE INFLUENCE OF GREEN HUMAN RESOURCE MANAGEMENT AND GREEN ORGANIZATIONAL CULTURE ON GREEN EMPLOYEE BEHAVIOR WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT SELAMAT SEMPURNA Tbk - Jordy, Steven; Hamdani (Cahaya Ilmu Bangsa, 2025)
This research aims to analyze the influence of Green Human Resource Management and Green Organizational Culture on Green Employee Behavior with Job Satisfaction as an Intervening Variable. This research uses a quantitative approach with a survey method involving a sample of 85 employee respondents who work at PT Selamat Selamat Tbk. Data was collected through a questionnaire which was measured using a Likert scale. Data analysis was carried out using the SmartPLS V.4.0 application to test direct and indirect relationships between variables. The research results show that: 1) Green Human Resource Management has a positive and significant effect on Job Satisfaction. 2) Green Organizational Culture has a positive and significant effect on Job Satisfaction. 3) Green Human Resource Management has a positive and significant effect on Green Employee Behavior. 4) Green Organizational Culture has a significant positive effect on Green Employee Behavior. 5) Job Satisfaction has a positive and significant effect on Green Employee Behavior. 6) Job Satisfaction cannot mediate the influence of Green Human Resource Management on Green Employee Behavior. (7) Job Satisfaction cannot mediate the influence of Green Organizational Culture on Green Employee Behavior.